2021
DOI: 10.1519/jsc.0000000000003087
|View full text |Cite
|
Sign up to set email alerts
|

Altered Physical Performance Following Advanced Special Operations Tactical Training

Abstract: The purpose of this study was to determine how the unique challenges of specific military tactical training phases influence overall physical performance characteristics. Broad jump, 5-10-5, 300-yd shuttle, percent body fat (%BF), anaerobic power (AP) and anaerobic capacity (AC), maximal oxygen uptake (V Ȯ2 max), isokinetic knee extension/flexion strength, shoulder internal/external rotation strength, and trunk extension/flexion strength were collected on 73 United States Marine Corps Forces Special Operations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Significant phase-specific changes in overall physical performance were observed during the individualised training course, including decreases in body fat percentage, anaerobic capacity, and maximal oxygen uptake. Current performance training during the course improves critical strength and power aspects [34].…”
Section: Discussionmentioning
confidence: 99%
“…Significant phase-specific changes in overall physical performance were observed during the individualised training course, including decreases in body fat percentage, anaerobic capacity, and maximal oxygen uptake. Current performance training during the course improves critical strength and power aspects [34].…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative effect of learning the necessary physically demanding job-specific skills (e.g., defensive tactics for law enforcement trainee and firefighting techniques for firefighter trainees) could have deleterious effects on fitness for the trainee. For instance, Winters et al (74) reported that intensive job-specific skill training in Marine Raider students decreased aerobic capacity and shoulder external rotation strength. Therefore, the trainee must have the physical resilience to withstand the combination of general fitness and job-specific skills training.…”
Section: The Training Academymentioning
confidence: 99%
“…Demands often faced by tactical personnel include exposure to extreme environments, maneuvering across difficult and unpredictable terrain, heavy load carriage, disaster response, evading human threats, evacuating casualties, and many other tasks that require intense physical labor in austere environments [ 1 , 2 , 3 ]. As such, the rigorous nature of the profession exposes individuals to multiple stressors that can have a negative impact on performance characteristics that are critical to the duties they must carry out [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even the smallest performance decrement could potentially be life threatening to the individual and others around them. Therefore, a high level of performance while overcoming various threats is critical for successful achievement of task and mission objectives [ 1 , 3 , 4 ]. Additionally, the long-term health and resilience of these personnel are dependent upon their ability to tolerate these demands and respond to stressors over time.…”
Section: Introductionmentioning
confidence: 99%